INTELLECTUAL CAPITAL AND EARNINGS QUALITY, THE MODERATING ROLE OF POLITICAL CONNECTIONS IN JORDAN. - Alorayni, Osamah Jamal; Ganesan, Yuvaraj; Hashim, Fathyah (The journal of contemporary issues in business and government, 2024)
The separation of ownership from management in corporations has led to the emergence of entities where the interests of multiple related parties may conflict. Financial reports serve as reflections that demonstrate the level of profitability of these companies and provide the primary source of information that can be utilized by various stakeholders in evaluating their performance, predicting their sustainability, cash flow projections, etc. Consequently, earnings quality plays a significant role in attracting investments and fostering economic growth in countries. As Jordan is a developing nation striving to attract investments and open up to the world, this study investigates the factors influencing the level of earnings quality, particularly after reviewing previous literature indicating a decline in earnings quality in Jordan. The study adopts a research model that aligns with the agency and resource independence theories aimed at bridging the gap and elucidating the contrasting findings of previous literature by examining the roles of intellectual capital components in effect earnings quality, particularly considering that the Jordanian legislature does not require any form of disclosure for intellectual capital by Jordanian firms. Furthermore, the study explores the moderating role of political connections on the study's relationships. To achieve the study's objectives, the sample consists of non-financial Jordanian firms listed on the Amman Stock Exchange (ASE) from 2017 to 2020, and the modified Jones model (1995) was used as a proxy to measure earnings quality. Moreover, the research findings indicated that human capital has statistically significant effects on earnings quality, while the remaining variables were not. Likewise, pertaining to the moderator effect of political connection, the results showed that political connection significantly moderates the relationship between the structure capital, relational capital, and earnings quality. Finally, this study can serve as a guide for regulatory bodies such as the Jordan Securities Commission and Amman Stock Exchange in order to formulate new strategies and policies. Furthermore, this study is able to enhance the knowledge of academic researchers by filling up the gap in the literature.